California Sketches, New Series - Fitzgerald, O. P. (Oscar Penn), 1829-1911 (Salt Lake City, UT : Project Gutenberg, 2004)
"California Sketches, New Series" by O. P. Fitzgerald is a collection of literary sketches written in the late 19th century. The book depicts various characters and scenarios highlighting life in California during its pioneering days, often reflecting on the complexities of human nature, social issues, and the author's personal experiences in the newly settled regions of the West. The opening of this work introduces the reader to a nostalgic perspective on California's past, as the narrator reminisces about familiar faces from his youth and reflects on the challenges and joys of life in the burgeoning state. Specifically, the initial sketches portray various figures, such as a teacher and a beloved turkey named Dick, against a backdrop of social commentary on family dynamics and individual struggles within the community. Through evocative language and keen observation, Fitzgerald brings to life the diverse tapestry of characters that inhabited California, setting the stage for further explorations of the human condition intertwined with the spirit of the frontier. (This is an automatically generated summary.)
Release date is 2004-06-01
Produced by David A. Schwan
Keywords: California -- Social life and customs; California -- Description and travel; Law -- Political aspects -- California; Ethnic groups -- California; Religion and ethics -- California